'Àdah Makkatte' bi Sulawesi al Janūbiyah: Bayna al Ta'àlim al Dìniyyah wa al Taqàlid al Mahalliyah - Yasin, Yuli; Shuhufi, Nadyatul Hikmah; Ishmatul Maula, Fiina (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2022)
This research discusses about one of the customs or social traditions practiced by Muslim community in South Sulawesi. This tradition is called “Makkatte”. It is said that this tradition stems from the teachings of Islam, which includes a ceremony of female circumcision. It is well known that female circumcision has become subject for public debate and discussion in our present era, after the classical Muslim jurists agreed on its legitimacy, despite of their differences in its ruling, whether such a practice is considered a religious obligation or Sunnah. This research aims to define the Makkatte tradition and its status in the South Sulawesi community, in addition to its rule in the Islamic jurisprudence. This research adopts the descriptive and analytical method that allows researcher to obtain information, documents and folk narratives. This research also used field work method by making interviews with relevant sources and distributing questionnaires in 16 regions in South Sulawesi. One of the most important findings from this research is that Makkatte is a ceremony that includes ablution, pronouncement of shahada, reciting some verses of the Qur’an, and female circumcision. In its ritual process, Makkatte is most often performed by a person known as Sanro, which means midwife according to the Bugis language in Sulawesi. The majority of the Muslim community in South Sulawesi agreed that the tradition of Makkatte is an obligation on every female, as it includes shahada and circumcision. This study also affirms that the additional customary ceremonies to Makkatte does not affect the fact that it is in compliance with God Almighty's command to circumcise females.